REGIONAL GEOMORPHOLOGICAL RESEARCHES (MORPHOHRONODYNAMIC DIRECTION) - Komliev, O.; Dovnich, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Regional studies in geomorphology are historically determined by basic concepts and paradigms for the moment. The current morphogenetic and morphodynamic concepts do not comply with the achieved level of theoretical geomorphology and other sciences, collected data, opportunities for solution of various global and regional problems. New generalization concept of geomorphology has been considered – morphochronodynamic: theory, methodology, applied directions, experience of using it in regional geomorphological studies of historical and dynamic basinal geomorphposystems.
Keywords: regional studies, theory of geomorphology, morphochronodynamic conception, historical and dynamic basinal geomorphosystems